Modelagem espacial dos atributos do solo sob diferentes ocupações em uma microbacia perene de vertente do semiárido - Oliveira Júnior, Raimundo Fernandes de (Universidade Federal Rural do Semi-Árido, 2016)
Knowledge of the use and occupation of land and water management is extremely necessary for an integrated and sustainable management of its resources, particularly water and soil. Allied to this, the spatial distribution of soil properties play a fundamental role in the design and understanding of human impacts on watersheds. Then, describe and map the land use and occupation with the spatial variability of its attributes is very important to put into practice techniques of rational and appropriate management of exploitation of these resources. Geostatistics has contributed increasingly to space research soil attributes. Therefore, the objective of this work dissertation was to map the use and occupation of land along with their attributes, using GIS and geostatistics, a perennial watershed shed in semi-arid conditions. The watershed of pecks Creek belongs to the middle reaches of the river basin of Apodi-Mossoró River, located in the west of Rio Grande do Norte state. inderformadas and misshapen collected soil to carry out the laboratory of physical water and soil chemical attributes analyzes were performed. The study showed that the use of geostatistics was suitable for the measurement of the spatial dependence of soil properties in a watershed, with the theoretical models, exponential and spherical, who played better results. Among the attributes of the soil studied the chemicals suffered greater interference of human impacts in the area. With this work it was possible to conclude that the map of land use and occupation, along with maps of spatial variability of soil attributes, proved to be a powerful assessment tool of environmental impacts on watersheds and contribute to the planning rational use and land use in watersheds sustainably
Keywords: Uso e ocupação do solo; Geoestatística; Krigagem; Atributos do solo; Use and occupation of soil; Geostatistics; Kriging; Soil properties; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO